Successful repair of neonatal tricuspid regurgitation due to chordae rupture - Pan, Jun-Yen (J Thorac Dis, 2018)
Neonatal rupture of the chordae of tricuspid valve with severe regurgitation is rare and disastrous. We report on a full-term female neonate presented with cyanosis caused by severe tricuspid regurgitation (TR) due to anterior leaflet chordal rupture. After initial stabilization by prostaglandin E1 infusion, successful early repair was achieved with artificial chordae implantation. The unique pathophysiology and the therapeutic strategy of this situation will be described.